2022
DOI: 10.1002/em.22522
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental contaminants on extracellular vesicles and their key molecular regulators: A literature and database‐driven review

Abstract: Exposure to environmental chemicals is now well recognized as a significant factor contributing to the global burden of disease; however, there remain critical gaps in understanding the types of biological mechanisms that link environmental chemicals to adverse health outcomes. One type of mechanism that remains understudied involves extracellular vesicles (EVs), representing small cell-derived particles capable of carrying molecular signals such as RNAs, miRNAs, proteins, lipids, and chemicals through biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…An increasing amount of evidence suggests that environmental pollutants can modify the production of EVs, and that they are involved in the appearance or progression of diseases linked to environmental exposures including lung cancer [ 314 ]. Tobacco-smoke, PM 2.5 and PAHs have been shown to trigger EV release from different lung cell types (macrophages, bronchial epithelial cells, endothelial cells, platelets) [ 315 ].…”
Section: Cancer Promotion Including Cell-to-cell Communication Egfr A...mentioning
confidence: 99%
“…An increasing amount of evidence suggests that environmental pollutants can modify the production of EVs, and that they are involved in the appearance or progression of diseases linked to environmental exposures including lung cancer [ 314 ]. Tobacco-smoke, PM 2.5 and PAHs have been shown to trigger EV release from different lung cell types (macrophages, bronchial epithelial cells, endothelial cells, platelets) [ 315 ].…”
Section: Cancer Promotion Including Cell-to-cell Communication Egfr A...mentioning
confidence: 99%
“…Recent research has shown that EVs may mediate the effects of exposure to environmental stressors. 3 6 But exactly how this works, and how such knowledge could be used to monitor and assess health effects of pollutant exposures, is largely unknown and a subject of increasing interest.…”
mentioning
confidence: 99%